THE ROLE OF TNF-Î± AND IL-6 CYTOKINE IN CHILDREN WITH STATUS EPILEPTICUS - Wibowo, Agung Prasetyo; Sujuti, Hidayat; Rahayu, Masruroh; Muid, Masdar; Kawuryan, Siti Lintang (Malang Neurology Journal, 2018)
Background. One of pediatric emergencies that has high mortality is status epilepticus (SE). Correlation between tumor necrosis factor (TNF)-Î±, interleukin (IL)-6, and SE had been reported but human study of it is limited. Objective. To compare TNF-Î± and IL-6 level in children with SE to those of children without SE and to find correlation between both cytokines.Methods. Cross-sectional study was conducted in dr.Saiful Anwar Hospital Malang with 48 children were enrolled in this study. All subjects were divided into three groups, including children who had SE; children who had seizure but not SE; and children who have no seizure. The levels of TNF-Î± and IL-6 serum were measured by ELISA.Results. TNF-Î± and IL-6 serum level were not significantly different between groups (p=0.920, p=0.829). We found interesting fact that the level of IL-6 in children with SE who have no disability was significantly higher than that of children who died or had disability (p=0.015). There was strong correlation between TNF-Î± and IL-6 in SE group (R 2 = 0.841 and p = 0.0001).Conclusion. IL-6 serum level was higher in SE children who have no disability and correlate with TNF-Î± serum level.